Epiphytism of Gracilaria cliftonii (Withell, Millar & Kraft) from Western Australia - Munoz, Julieta; Fotedar, Ravi (Springer, 2009)
Epiphytism in Gracilaria is a common phenomena observed in natural populations and under culture conditions. Generally, epiphytes are attached superficially to the surface of the host however, genera such as Polysiphonia spp. and Ceramium spp. can penetrate into the host tissue affecting its growth and hence productivity. The present paper aims to identify and quantify epiphyte abundance and characterise their attachment and penetration on the natural populations of Gracilaria cliftonii collected from Shoalwater Marine Park, Perth, Western Australia. G. cliftonii samples were collected monthly for 1 year and their epiphytes were identified. Histological studies of G. cliftonii were also performed on epiphyte attachment sites. Twenty-four species of macroalgae epiphytes were recorded, 21 belonging to Rhodophyta and 3 to Chlorophyta. Hypnea episcopalis and Polysiphonia forfex were the dominant (p<0.05) species during the sampling period. The maximum epiphytic load was observed in October (40%), however, the maximum diversity of epiphytes was recorded in September and February (n=14). Light and scanning electron microscopy studies of the epiphyte attachment sites revealed that P.forfex and Ceramium isogonum penetrated into the cortex and outer medulla of G. cliftonii, while Bryopsis plumosa and Laurencia clavata altered the cellular structure of the cell wall of G. cliftonii.